IMPLEMENTASI SKEMA SLEEP-WAKEUP PADA JARINGAN SENSOR NIRKABEL MELALUI MEDIA BLUETOOTH - , RIJDZUAN ADI SAMPOERNA, Drs. Bambang Nurcahyo Prastowo, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development in technology world has broaden the capability of small sensor in embedded system to connect the internet. Internet of Things (IoT) is the popular term in Wireless Sensor Network to coin this phenomenon. Wearable device is one of the implementation from IoT. The needs to track all the activities done by a single human being, demand a continuous data flow, which is lead to several problems. One of the main problem is power consumption. In this research, sleep-wakeup scheme was implemented as data transmision method between node sensor and Android device. The research focused on the side effect caused by sleep-wakeup scheme over conventional method on data transmission. Sleep-wakeup scheme implemented by scheduling the connecting and disconnecting of socket connection from both devices. Some condition applied to each experiment in order to obtain the accuracy and time response of the system. The result stated that sleep-wakeupâs accuracy is 78%-94% which is lower than conventional data transmissionâs accuracy recorded at 91%-99% of data correct received. The lower accuracy that sleep-wakeup have are caused by the broken data located in the beginning of wakeup periode. Time response needed to create a socket of bluetooth after less than or equal to 2 seconds are in between 0.55 seconds to 0.62 seconds. Meanwhile, time response needed to create a socket of bluetooth for more than 2 seconds takes longer in around 0.96 seconds to 4.19 seconds.